Kampung Madinah: The Construction of Jamaah Tabligh for the Arabization Process in Magetan, East Java - Mustaqim Pabbajah; Nur Quma Laila; Terachai Ponnui; Siti Aisyah Sungkilang; Juhansar Juhansar (Faculty of Social and Political Sciences - UIN Walisongo Semarang, 2022)
Arabization is not always identically carried out by immigrants of Arab descent, but non-Arab communities can carry out the Arabization process. This study aims to explain the Arabization process by the Jamaah Tabligh (JT) group by establishing the Kampung Madinah of Temboro Village. This study collects qualitative data through observation, interviews, and a literature study with descriptive analysis. The findings show that the existence of JT in Temboro Village has resulted in a shift in community culture from secular to religious. The role of the JT leadership became an emerging factor in the Arabization process in forming a religious society. Likewise, JT's persuasive approach through education and religious activities facilitates public acceptance. The naming of Kampung Madinah in Temboro is driven by various Arabic symbols used, e.g., daily conversations, activities, and clothes. The existence of JT succeeds in constructing Temboro people's habits into “Islamic habits.” This study is limited to Kampung Madinah in Temboro as a research focus; therefore, it is recommended that further researchers conduct comparative studies on the Arabization process.